Stat. of Ohio & N.W. Terr. 106, ch 14, § 4 (Vol. 1, 1833) - (:unkn) unknown (My University, 1790)
§That if any person shall presume to discharge or fire, or cause to be discharged or fired, any gun or other fire-arms at any mark or object, or upon any pretence whatever, unless he or she shall at the same time be with such gun or fire-arms at the distance of at least one-quarter of a mile from the nearest building of any such city, town, village or station, such person shall for every such offence, forfeit and pay to the use of the county in which the same shall be committed, a sum not exceeding five dollars, not less than one dollar
Keywords: DISCHARGE